Quantitative determination of linking number differences between circular polynucleosomes and histone H1-bound circular polynucleosomes - Zhang, Hao (2019)
With the aim of discovering contribution of histone H1 to linking number changes of DNA, determination of linking number differences between histone H1-free circular polynucleosomes and histone H1-bound circular polynucleosomes was carried out during our investigations. Our results showed that on average, binding of ∼11.5 histone H1 molecules causes one linking number change in circular polynucleosomes in the presence of 1.5 mM spermidine. When concentrations of spermidine decreases or increases, these linking number differences decrease significantly. It is therefore evident that linking number changes caused by histone H1 are spermidine concentration-dependent.